'The law comes first?': the dynamics of victims' redress in Bosnia and Herzegovina. Issue 1 (2nd January 2023) - Barton Hronešová, Jessie
ABSTRACT: What explains the variety in victim-centric state policies of redress in postwar Bosnia and Herzegovina (BiH)? Rather than analyzing BiH as a special case of a divided ethno-national state, this article studies domestic victimhood politics as a phenomenon with wider comparative applications for post-conflict contexts. Redress, a set of policies that legally recognize victims/survivors of wartime atrocities and provide them with in-kind and financial support, has increasingly entered the demands of victims/survivors. Many have sought to expand their rights through new legal frameworks at the state and subnational levels. However, in the Bosnian case only some have succeeded (or partially succeeded) with their demands. Why? Using fieldwork data and relying on literature in transitional justice, identity and peacebuilding, I argue that the differences go beyond ethno-national divisions and identity politics and are explained by how victims/survivors utilize their victim capital that combines mobilization resources, moral authority and international salience.